Mass Balance Evolution of Black Rapids Glacier, Alaska, 1980–2100, and Its Implications for Surge Recurrence - Kienholz, Christian; Hock, Regine; Truffer, Martin; Bieniek, Peter; Lader, Richard (Frontiers in Earth Science, 2017)
Surge-type Black Rapids Glacier, Alaska, has undergone strong retreat since it last surged in 1936-37. To assess its evolution during the late 20th and 21st centuries and determine potential implications for surge likelihood, we run a simplified glacier model over the periods 1980-2015 (hindcasting) and 2015-2100 (forecasting). The model is forced by daily temperature and precipitation fields, with downscaled reanalysis data used for the hindcasting. A constant climate scenario and an RCP 8.5 scenario based on the GFDL-CM3 climate model are employed for the forecasting. Debris evolution is accounted for by a debris layer time series derived from satellite imagery (hindcasting) and a parametrized debris evolution model (forecasting). A retreat model accounts for the evolution of the glacier geometry. Model calibration, validation and parametrization rely on an extensive set of in situ and remotely sensed observations. To explore uncertainties in our projections, we run the glacier model in a Monte Carlo fashion, varying key model parameters and input data within plausible ranges. Our results for the hindcasting period indicate a negative mass balance trend, caused by atmospheric warming in the summer, precipitation decrease in the winter and surface elevation lowering (climate-elevation feedback), which exceed the moderating effects from increasing debris cover and glacier retreat. Without the 2002 rockslide deposits on Black Rapids' lower reaches, the mass balances would be more negative, by ~20% between the 2003 and 2015 mass-balance years. Despite its retreat, Black Rapids Glacier is substantially out of balance with the current climate. By 2100, ~8% of Black Rapids' 1980 area are projected to vanish under the constant climate scenario and ~73% under the RCP 8.5 scenario. For both scenarios, the remaining glacier portions are out of balance, suggesting continued retreat after 2100. Due to mass starvation, a surge in the 21st century is unlikely. The projected retreat will affect the glacier's runoff and change the landscape in the Black Rapids area markedly.